Killer whales wolves of the sea - Parer, David; Attenborough, David, 1926- (Washington, D.C. : National Geographic Society, 1993)
Shows killer whales in the wild and in oceanariums, and describes their physical and mental characteristics, physiology and bahaviour. Discusses the latest scientific research on these ocean mammals
Narrator: David Attenborough
Keywords: Killer whale; Whales